Identification of the ball mill ore loading according to the parameters of energy efficiency of material destruction - Kondratets, V. O.; Karchevska, M. O. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The results of theoretical research are presented and an algorithm for the identification of a ball mill ore loading according to the parameters of energy efficiency of material destruction is suggested in the paper.